A short history of early modern England : British literature in context - Herman, Peter C., 1958-; Wiley InterScience (Online service) (Chichester, West Sussex, U.K. ; Malden, MA : Wiley-Blackwell, 2011)
"A Short History of Early Modern England presents the historical and cultural information necessary for a richer understanding of English Renaissance literature. Written in a clear and accessible style for an undergraduate level audience Gives an overview of the period's history as well as an understanding of the historiographic issues Explores key historical and literary events, from the Wars of the Roses to the publication of John Milton's Paradise Regained Features in depth explanations of key terms and concepts, such as absolutism and the Elizabethan Settlement "--
"The English Renaissance produced some of the greatest literary works the world has ever known, from the Faerie Queene and Paradise Lost to Hamlet and Macbeth. A Short History of Early Modern England presents students with the crucial historical and cultural information necessary for a richer appreciation and deeper understanding of the literature produced in this period. Following an overview of England's political and social structures, subsequent chapters explore key historical and literary events, from the Wars of the Roses to the publication of John Milton's Paradise Regained and Samson Agonistes, with particular attention to the major political and religious developments throughout this transformative era. Written in a clear and accessible style, this is the perfect text to help students familiarize themselves with this remarkable period in English literary history"--
Machine generated contents note: Aims and Acknowledgements -- Quoting from Early Modern Texts -- Illustrations -- Rulers of England and Timeline of Key Events -- 1: An Overview of Early Modern England -- 2: The Back-Story of the Tudor Dynasty: From Richard II to Henry VII -- 3: Henry VII, Henry VIII, and the Henrician Era (1509-1547) -- 4: Edward VI, Lady Jane Grey, and Mary I (1547-1553) -- 5: The Elizabethan Era (1558-1603) -- 6: The Reign of King James VI/I (1603-25) -- 7: Charles I (1625-1642): from Accession to the Beginning of the Civil Wars -- 8: The Civil Wars, the Commonwealth, and the Early Restoration (1642-1671).
Includes bibliographical references and index.
Electronic reproduction.
Keywords: 1485 - 1714; English literature -- Early modern, 1500-1700.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; English literature -- Early modern; Englisch; Literatur; Zeithintergrund; Great Britain -- History -- Tudors, 1485-1603.; Great Britain -- History -- Stuarts, 1603-1714.; Great Britain; Electronic books; History